(untitled) (Bangladesh Journal of Agricultural Research, 2009)
The field experiment was conducted during the rabi season of 2005-06 in the farmer’s field of Multi-location Testing (MLT) site, Melandah, Jamalpur to evaluate the performance of sweet potato varieties as well as to determine the optimum dose of fertilizer of sweet potato. Two varieties of sweet potato viz., i) BARI Sweet Potato-5 and ii) BARI Sweet Potato-7 and five fertilizer doses viz., i) Estimated fertilizer dose for average yield goal (EDI for average yield goal), ii) Integrated Plant Nutrient System (IPNS) basis fertilizer dose, iii) Fertilizer Recommendation Guide’ 97, iv) Farmer’s practice, and v) Control. The highest sweet potato yield was obtained from BARI SP-7 with (IPNS) basis fertilizer doses (33.9 t/ha). The lowest sweet potato yield was obtained from BARI SP-7 with control treatment. The highest gross return (112700 Tk./ha) and gross margin (10756 Tk./ha) was recorded from IPNS basis fertilizer treatment. The lowest gross return (40950 Tk./ha) and gross margin (40951) Tk./ha) was recorded from control treatment. But the cost and return analysis showed that the highest benefit cost ratio (24.95) and marginal rate of return (1452) was found from FRG/97 treatment due to lower additional cost. Key Words: Fertilizer, IPNS, sweet potato varieties and yield. DOI: 10.3329/bjar.v34i3.3974 Bangladesh J. Agril. Res. 34(3) : 473-480, September 2009